2016
DOI: 10.1371/journal.pone.0168731
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Chemotherapy Does Not Disrupt Orexin Signaling

Abstract: BackgroundSteroid-induced sleep disturbance is a common and highly distressing morbidity for children receiving steroid chemotherapy for the treatment of pediatric acute lymphoblastic leukemia (ALL). Sleep disturbance can negatively impact overall quality of life, neurodevelopment, memory consolidation, and wound healing. Hypothalamic orexin neurons are influential wake-promoting neurons, and disturbances in orexin signaling leads to abnormal sleep behavior. A new class of drug, the orexin receptor antagonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Dexamethasone chemotherapy did not block the orexinergic signaling in children with acute lymphoblastic leukemia; the same finding was observed in rodents [84]. Thus, a high dose of dexamethasone did not disrupt the human orexin physiology and this system was well preserved (e.g., OXR expression and neural output).…”
Section: Acute Lymphoblastic Leukemiasupporting
confidence: 53%
See 1 more Smart Citation
“…Dexamethasone chemotherapy did not block the orexinergic signaling in children with acute lymphoblastic leukemia; the same finding was observed in rodents [84]. Thus, a high dose of dexamethasone did not disrupt the human orexin physiology and this system was well preserved (e.g., OXR expression and neural output).…”
Section: Acute Lymphoblastic Leukemiasupporting
confidence: 53%
“…Dexamethasone chemotherapy did not block the orexinergic signaling. [84,85] Adrenocortical adenoma Prepro-orexin mRNA, orexin A (not orexin B) and OXR1/OXR2 upregulation. Orexin A, but not orexin B, augmented normal/adrenocortical adenoma cell proliferation.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…The activity of each neural system under steroid administration is not fully understood, but several pieces of evidence indicate that some neurons and neurotransmitters are affected, and others are not affected by DXM administration. Regarding orexin neurons, which are known as the principal component of the wakefulness-promoting system [ 10 , 21 , 22 ], a previous study showed that the concentration of orexin protein concentration in the hypothalamus does not change even under DXM administration (5 d at a concentration of 1.5 mg/kg); this indicates that the output of the orexin neuron does not change following DXM administration in mice [ 23 ]. Another study shows that intramuscular DXM administration (7 d at a concentration of 1 mg/kg) increased noradrenaline and decreased adrenaline levels and did not alter the serotonin level of the pineal-paraphyseal complex in Lissemys punctata punctata [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…under DXM administration (5 d at a concentration of 1.5 mg/kg); this indicates that the output of the orexin neuron does not change following DXM administration in mice [23]. Another study shows that intramuscular DXM administration (7 d at a concentration of 1 mg/kg) increased noradrenaline and decreased adrenaline levels and did not alter the serotonin level of the pineal-paraphyseal complex in Lissemys punctata punctata [24].…”
Section: Plos Onementioning
confidence: 95%
“…However, this effect was specifically evaluated in a recent study in children with acute lymphoblastic leukemia, which showed that cerebral spinal fluid orexin levels (SD) were not significantly different from baseline after dexamethasone administration: 574 (26.6) pg/mL vs 580 (126.1) pg/mL; P = .8. 45…”
Section: Hpa Axis Modificationmentioning
confidence: 99%